2000
DOI: 10.1103/physrevlett.84.2722
|View full text |Cite
|
Sign up to set email alerts
|

Inseparability Criterion for Continuous Variable Systems

Abstract: An inseparability criterion based on the total variance of a pair of Einstein-Podolsky-Rosen type operators is proposed for continuous variable systems. The criterion provides a sufficient condition for entanglement of any two-party continuous variable states. Furthermore, for all Gaussian states, this criterion turns out to be a necessary and sufficient condition for inseparability.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
2,181
2
22

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,945 publications
(2,250 citation statements)
references
References 16 publications
28
2,181
2
22
Order By: Relevance
“…Any two-mode state can be fully described by a covariance matrix (assuming for simplicity that its mean value is 0), which in standard form [21,22] is written as…”
Section: Gaussian Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Any two-mode state can be fully described by a covariance matrix (assuming for simplicity that its mean value is 0), which in standard form [21,22] is written as…”
Section: Gaussian Statesmentioning
confidence: 99%
“…By applying S 2 (r) to a couple of vacuums, we obtain a pure state called the two-mode squeezed vacuum, with a = b = [15]. The necessary and sufficient separability criterion for a two-mode Gaussian state σ has been shown to be the positivity of the partial transposed stateσ [21][22][23]. This is equivalent to checking the conditionν − 1 [10], whereν − is the lowest symplectic eigenvalue ofσ .…”
Section: Gaussian Statesmentioning
confidence: 99%
“…Since we are working with Gaussian states, there are necessary and sufficient criterion to determine if the state is entangled [16][17][18]. Simon [16] has shown that for any two-mode Gaussian state, if the following inequality is observed…”
Section: General Properties Of Two-mode Gaussian Statesmentioning
confidence: 99%
“…For the present system, this allows us to consider continuous-variable bipartite entanglement [10,11] and demonstra- tions of the Einstein-Podolsky-Rosen paradox [14], more recently labelled steering [26]. Asymmetric Gaussian steering has previously been theoretically analysed using an unbalanced nonlinear coupler [27] and experimentally produced using parametric downconversion [28].…”
Section: Entanglement and Epr For Different Input Statesmentioning
confidence: 99%